Contributory Pension Scheme and Insurance Industry’s Equity Investments in Nigeria - Odo, Cosmas Ogobuchi; Okeke, Chinedu Crescent; Okoro, Deborah Patience (Archives of Business Research, 2022)
The paper explores the nexus between contributory pension and growth of the Nigerian insurance industry. Proxies for insurance industry growth were taken as direct premium generated and growth of its investments, especially equity investments. Given that equity investment was one of the prescribed investment outlets for insurance industry funds in Nigeria, authors hypothesized that the contributory pension Act of 2014 would spur rapid growth in equity investments of the industry for the period investigated. Ex-post facto research design was followed and data were drawn from the annual accounts and reports of National Insurance Commission, NAICOM, and publications of Pension Regulatory Commission, PENCOM, National Bureau of Statistics, NBC, and Central Bank of Nigeria, CBN, for the period, 2005-2015. Ordinary Least Square (OLS) was the estimation method, whereas techniques for data analysis included Multi-Regression model, t-test statistic, adjusted coefficient of determination and F-statistic. The result of the tests showed that contributory pension has positive and significant impact on the insurance industry’s equity investments (p<0.05). Clearly, reform of pension industry led to rapid increases in the equity investments of the insurance industry but limited only by statutory ceiling on equity investments and what sound prudence dictates.